Ferulic acid encapsulated chitosan‐tripolyphosphate nanoparticles attenuate quorum sensing regulated virulence and biofilm formation in Pseudomonas aeruginosa PAO1. Issue 8 (22nd August 2018) - Pattnaik, Subhaswaraj; Barik, Subhashree; Muralitharan, Gangatharan; Busi, Siddhardha
Abstract : Pseudomonas aeruginosa is an opportunistic nosocomial pathogenic microorganism causing majority of acute hospital‐acquired infections and poses a serious public health concern. The persistence of bacterial infection can be attributed to the highly synchronised cell‐to‐cell communication phenomenon, quorum sensing (QS) which regulates the expression of a number of virulence factors and biofilm formation which eventually imparts resistance to the conventional antimicrobial therapy. In this study, the anti‐quorum sensing and anti‐biofilm potential of ferulic acid encapsulated chitosan‐tripolyphosphate nanoparticles (FANPs) was investigated against P. aeruginosa PAO1 and compared with native ferulic acid. Dynamic light scattering and transmission electron microscopic analysis confirmed the synthesis of FANPs with mean diameter of 215.55 nm. FANPs showed significant anti‐quorum sensing activity by downregulating QS‐regulated virulence factors. In addition, FANPs also significantly attenuate the swimming and swarming motility of P. aeruginosa PAO1. The anti‐biofilm efficacy of FANPs as compared to native ferulic acid was established by light and confocal laser scanning microscopic analysis. The promising results of FANPs in attenuating QS highlighted the slow and sustained release of ferulic acid at the target sites with greater efficacy suggesting its application towards the development of anti‐infective agents.